C2 Induced pluripotent stem cells (IPSC) as a model of huntington's disease. (13th September 2016) - Rosati, Jessica; Bidollari, Eris; Tardivo, Silvia; Marano, Massimo; Sabarese, Giovanna; Altieri, Filomena; Vescovi, Angelo Luigi; Squitieri, Ferdinando
Abstract : Background and rationale: Huntington's disease (HD) patients' cell lines may theoretically offer the opportunity to study longitudinal changes due to the mutated protein in its own physiological context. We are therefore exploring whether human induced pluripotent stem cells (iPSCs) from HD subjects represent a model to investigate the polyQ effects in vitro. Aims: 1) Creation of an iPS collection from HD subjects; 2) Analysis of neural functions in reprogrammed cell lines, according to the different repeat sizes. Methods: Patient's skin fibroblasts were reprogrammed into iPSCs introducing four pluripotency episomal factors (SOX2, KLF4, c-MYC AND OCT4) by virus-free protocol. All iPS clones that show an uniform flat morphology were characterised for their stemness and pluripotency, both in vitro through embryoid bodies formation and in vivo through teratoma formation assay. A new protocol was optimised for differentiation of iPCs derived embryoid bodies expressing all the three germ layers (ectoderm, mesoderm and endoderm) in neurospheres of Neuronal Precursor Cells (NPCs) (Vescovi et al ., 1999). We may obtain a neural population of astrocytes, oligodendrocytes and neuron cells by spontaneous differentiation of neurospheres in particular conditions. Results: We have now obtained skin biopsies from 20 mutation positive subjects (from pre- to advanced HD stages) and five controls, at IRCCS Casa Sollievo della Sofferenza, Mendel Institute of Human Genetics, based in Rome. As first step, we got samples from subjects carrying borderline (ie 36–40 CAG) and very high (over 60) repeats. Conclusion: We expect this model will allow us to highlight polyQ dependent changes in neural function and differentiation, in vitro.